Improving Students’ Vocabulary Mastery by Using Crossword Puzzle Technique - Sindi Maulidia; Muhammad Mugni Assapari; Soni Ariawan (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2025)
Many high school students face several challenges in mastering vocabulary. Students need help to improve their English vocabulary mastery and need more self-confidence. The crossword puzzle technique was used in this study to enhance students' vocabulary mastery at SMKS Tarbiyatul Qurro. This study employed Classroom Action Research with 20 students in second grade. Observation and tests were used as instruments for data collection. This study shows that applying the crossword puzzle technique can improve students' vocabulary mastery. The student's vocabulary mastery showed significant improvement, as evidenced by the increasing average scores from 55.25 in the pre-test to 67.75 in the post-test cycle 1 and 77 in the second cycle 2. On the other hand, in cycle 1, teacher observation results were 50%, which increased to 81.25% in cycle 2. This means that the teacher performed the crossword puzzle technique more frequently from cycle 1 to cycle 2. Similarly, student observation results improved from 56.25% in cycle 1 to 78.125% in cycle 2. This means that the students followed the crossword puzzle procedures more frequently from cycle 1 to cycle 2. In conclusion, the students' vocabulary mastery showed significant improvement through the application of the crossword puzzle technique.